Epicatechin Reduces Striatal MPP+-Induced Damage in Rats through Slight Increases in SOD-Cu, Zn Activity. (2nd August 2015) - Rubio-Osornio, M.; Gorostieta-Salas, E.; Montes, S.; Pérez-Severiano, F.; Rubio, C.; Gómez, C.; Ríos, C.; Guevara, J.
Abstract : Parkinson's disease is a neurodegenerative disorder characterized by movement alterations caused by reduced dopaminergic neurotransmission in the nigrostriatal pathway, presumably by oxidative stress (OS). MPP + intrastriatal injection leads to the overproduction of free radicals (FR). The increasing formation of FR produces OS, a decline in dopamine (DA) content, and behavioral disorders. Epicatechin (EC) has shown the ability to be FR scavenger, an antioxidant enzyme inductor, a redox state modulator, and transition metal chelator. Acute administration of 100 mg/kg of EC significantly prevented (P < 0.05 ) the circling MPP + -induced behavior (10  μ g/8  μ L). Likewise, EC significantly (P < 0.05 ) reduced the formation of fluorescent lipid products caused by MPP + . MPP + injection produced (P < 0.05 ) increased enzymatic activity of the constitutive nitric oxide synthase (cNOS). This effect was blocked with acute EC pretreatment. Cu/Zn-dependent superoxide dismutase (Cu/Zn-SOD) activity was significantly (P < 0.05 ) reduced as a consequence of MPP + damage. EC produced a slight increase (≈20%) in Cu/Zn-SOD activity in the control group. Such effects persisted in animals injured with MPP + . The results show that EC is effective against MPP + -induced biochemical and behavioral damage, which is possible by an increase in Cu/Zn-SOD activity.